The complete mitochondrial genome of Metapenaeus ensis. Issue 1 (2nd January 2019) - Yan, Maocang; Hu, Lihua; Zhang, Min; Ji, Dewei; Zhou, Qianjin; Zhang, Jiongming; Chen, Jiong
Abstract: The complete mitochondrial genome sequence of Metapenaeus ensis was obtained by PCR, containing 37 genes with 13 protein-coding genes, 22 transfer RNAs (tRNAs), two ribosomal RNAs (rRNAs) and a non-coding control region.